Clear skies or turbulence ahead? The international civil aviation organization’s obligation to mitigate climate change - Baine P. Kerr (Utrecht University School of Law, 2020)
The International Civil Aviation Organization (ICAO) set a cap for international aviation’s greenhouse gas (GHG) emissions at its 2020 level and established a market-based mechanism to help achieve that cap. Against that backdrop, this article identifies ICAO’s legal obligation to mitigate climate change by examining the international climate change treaties, ICAO’s constituent treaty, the Chicago Convention, and ICAO’s organizational practice. It finds that because ICAO is not a party to the climate change treaties and has a high degree of institutional autonomy, those treaties do not directly impose an obligation on ICAO. Although the Chicago Convention does not expressly mention the environment or climate change, ICAO’s member states interpreted the Convention and enlarged ICAO’s mandate under it to include the reduction or limitation of GHG emissions from international aviation so as to prevent dangerous climate change. This article finds that pursuant to Jan Klabbers’ recently developed theory of role responsibility, ICAO arguably has an obligation to carry out this important mandate, and its failure to do so, or failure to do so effectively, could constitute an internationally wrongful omission.